Cibercultura Informe al Consejo de Europa - Lévy, Pierre, 1956- (Autores, textos y temas. Ciencia, tecnología y sociedad, 2007)
"Needing guidance and seeking insight, the Council of Europe approached Pierre Lévy, one of the world's most important and well-respected theorists of digital culture, for a report on the state (and, frankly, the nature) of cyberspace. The result is this extraordinary document, a perfectly lucid and accessible description of cyberspace-from infrastructure to practical applications-along with an inspired, far-reaching exploration of its ramifications. A window on the digital world for the technologically timid, the book also offers a brilliant vision of the philosophical and social realities and possibilities of cyberspace for the adept and novice alike. In an overview, Lévy discusses the distinguishing features of cyberspace and cyberculture from anthropological, philosophical, cultural, and sociological points of view. An optimist about the future potential of cyberspace, he eloquently argues that technology-and specifically the infrastructure of cyberspace, the Internet-can have a transformative effect on global society. Some of the issues he takes up are new art forms; changes in relationships to knowledge, education, and training; the preservation of linguistic and cultural differences; the emergence and implications of collective intelligence; the problems of social exclusion; and the impact of new technology on the city and democracy in general. In considerable detail, Lévy describes the ways in which cyberspace will help promote the growth of democracy, primarily through the participation of individuals or groups. His analysis is enlivened by his own personal impressions of cyberculture-garnered from bulletin boards, mailing lists, virtual reality demonstrations, andsimulations. Immediate in its details, visionary in its scope, deeply informed yet free of unnecessary technical language, Cyberculture is the book we require in our digital age". -- From English edition.